Study, with Different Characterization Techniques, of the Formation of Cordierite from both Natural and Activated Algerian DD3 Kaolin. Issue 2 (2nd April 2020) - Kheloui, Meriem; Boumchedda, Khaled; Naitbouda, Abdelyamine
ABSTRACT: The work presented in this article deals with the synthesis of a cordierite ceramics, using a natural Algerian kaolin named DD3 of black colour, located in the region of Djbel Dbagh in Guelma. A synthesis was also carried out on bleached DD3 kaolin obtained by activation of hydrochloric acid on natural kaolin in order to eliminate the manganese oxide (which is responsible for the blackish colour) while enlarging the application field in industry (e.g. luxury porcelain). Preparation of this cordierite was carried out by adding the precipitated magnesium hydroxide and a silica deficit for each type of kaolin. Mixtures of pellet finely milled and pressed as pelleted powders were sintered at different temperatures (1150 o, 1250 o and 1350 o C) for 2 h before being characterized. The results obtained by X-ray diffraction showed that the cordierite phase crystallized at 1250 o C for both types of black and bleached samples, which was confirmed by Raman spectroscopy. Scanning electron microscopy was used to observe densification, homogeneity as well as the size of the sample constituents. Their coefficients of thermal expansion were respectively 1.95×10 –6 and 1.69×10 –6 o C –1 between 23 o and 800 o C, which allowed their use in automobile catalytic converters. GRAPHICAL ABSTRACT: